ASSESSING HORMONAL INFLUENCES ON TYPE 2 DIABETES IN POSTMENOPAUSAL WOMEN IN PAKISTAN: A PROSPECTIVE STUDY - Dr. Kashif Ali; Dr Bharat kumar; Dr Sabeen Arjumand; Dr Asma Ambreen; Naveed Alam; Dr Attaullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Type 2 diabetes mellitus [T2DM] is a significant public health concern worldwide, particularly in postmenopausal women who experience hormonal changes that may increase their risk. This study aimed to assess the hormonal influences on T2DM in postmenopausal women in Pakistan and evaluate the potential benefits of hormone replacement therapy [HRT] as a preventive strategy.Methods: A prospective cohort study was conducted at Department of Medicine, DG Khan Medical College DG khan, Pakistan, over one year from January 2023 to December 2023. A total of 128 postmenopausal women were included based on specific inclusion criteria. Participants were evaluated for their hormonal profiles, including levels of estradiol and sex hormone-binding globulin [SHBG], and their association with T2DM risk. The impact of HRT on T2DM incidence was also examined. Data were collected using standardized questionnaires and blood tests, and analyzed using appropriate statistical methods to identify significant associations.Results: The study found that lower levels of estradiol and SHBG were significantly associated with an increased risk of T2DM in postmenopausal women [p < 0.05]. Additionally, women who received HRT had a lower incidence of T2DM compared to non-users, suggesting a protective effect of HRT. The results underscore the importance of hormonal assessment in identifying women at higher risk for T2DM and highlight the potential of targeted interventions to prevent or delay diabetes onset.Conclusion: The findings of this study suggest that hormonal changes post-menopause significantly impact the risk of developing T2DM in Pakistani women. Monitoring hormonal levels and considering HRT as part of a comprehensive diabetes prevention strategy may be beneficial in reducing T2DM risk in this population. However, further research with larger sample sizes and diverse populations is necessary to validate these results and explore the long-term effects of hormonal therapies on diabetes prevention.